Ameliorative Role of Aqueous Saussurea lappa Root Extract in Tamoxifen-Induced Thyroid Dysfunction in Female Rats - Eman Ali Faraj Hamouda (Journal of Libyan Academy Bani Walid, 2025)
Background: This study was designed to evaluate the protective effects of Saussurea lappa aqueous root extract (SLRE) against tamoxifen (TMX)-induced thyroid dysfunction in adult female rats. Materials and Methods: Twenty-four adult female albino rats were randomly allocated into four groups (n = 6 per group): (1) control group receiving distilled water, (2) SLRE-treated group receiving 200 mg/kg, (3) TMX -treated group receiving 40 mg/kg, and (4) combined treatment group receiving both TMX (40 mg/kg) and SLRE (200 mg/kg). All treatments were administered orally via gavage once daily for 28 consecutive days. Serum levels of thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) were measured to assess thyroid function. Results: Administration of TMX resulted in significant thyroid dysfunction, characterized by elevated serum TSH levels and reduced concentrations of FT3 and FT4 compared to the control group (p = 0.001). Co-treatment with SLRE markedly ameliorated these hormonal disturbances, restoring thyroid hormone levels towards normal values (p = 0.001). The biochemical study was confirmed by histopathological investigation Conclusion: Tamoxifen induces thyroid dysfunction in adult female rats, whereas SLRE exhibits a protective effect by modulating thyroid hormone profiles. These findings suggest the potential of SLRE as an adjunct therapeutic agent for managing tamoxifen-induced thyroid dysfunction.